Battery module with polyorganosiloxane foam barrier
By using barrier materials of polyorganosiloxane foam, flame retardant and hollow ceramic particles in the battery module, the problem of insufficient thermal insulation in the high-energy density battery module is solved, and improved heat resistance and flame retardant performance is achieved, reducing the Fire and explosion risks.
Patent Information
- Application Number
- CN202280095723.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-09
- Publication Date
- 2024-12-13
AI Technical Summary
The existing thermal barrier materials are insufficient thermal insulation in high-energy density battery modules, which is difficult to prevent thermal runaway, and have poor mechanical properties, increasing the risk of fire and explosion.
A barrier material containing 35% to 95% by weight of polyorganosiloxane foam, 1% to 30% by weight of flame retardant and 1% to 35% by weight of hollow ceramic particles can be formed through a crosslinking network. Compressed, flame retardant and highly efficient thermal insulation foaming materials.
It provides improved heat resistance and flame retardant properties, reduces the risk of thermal runaway, and achieves a comprehensive effect of thermal insulation, flame retardancy and compressibility in high-energy density battery modules.
Smart Images

Figure CN119137198A_ABST
Abstract
Description
Background Art
[0001] The present invention relates to battery modules insulated with treated polyorganosiloxane foam barriers.
[0002] Rechargeable batteries such as lithium-ion batteries (LiBs) are commonly used in a variety of applications, including electric vehicles (EVs) and grid energy storage systems. Although LiBs have the desirable properties of high energy density and stability, safety issues currently limit their usefulness. First, failure of LiB cells can be triggered due to manufacturing defects, internal short circuits, overheating, overcharging, or mechanical shock; second, the heat generated from a failed cell can propagate, causing thermal runaway in adjacent cells. The rapid pressure buildup caused by these thermal events increases the risk of fire and explosion.
[0003] Thermal runaway can be mitigated by placing a thermal barrier between the cells in the LiB module, which provides thermal insulation and flame retardancy. Commonly used thermal barriers such as aerogels, ceramic fibers, and mica boards provide such properties; however, aerogels and ceramic fibers have poor mechanical elasticity, while mica boards have poor compressibility. On the other hand, although silicone foam foam provides sufficient compressibility and is therefore suitable for low and medium energy density batteries, its thermal insulation is insufficient to prevent thermal runaway for very high energy density battery packs. Therefore, in the field of thermal barriers for rechargeable batteries, it is desirable to produce a barrier that provides thermal insulation, flame retardancy, and satisfactory compressibility. Summary of the invention
[0004] The present invention solves the need in the art by providing a battery module comprising a housing containing an array of spatially separated battery cells and a barrier material contacting adjacent battery cells, wherein the barrier material comprises 35 wt % to 95 wt % polyorganosiloxane foam based on the weight of the barrier material; 1 wt % to 30 wt % flame retardant; and 1 wt % to 35 wt % hollow ceramic particles having a volume average particle size in the range of 25 μm to 300 μm; wherein the barrier material has a particle size of 0.10 g / cm 3 Up to 0.90g / cm 3 Density within the range.
[0005] The battery module of the present invention provides improved heat resistance and flame retardant properties for applications such as lithium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0006] Figure 1 is a diagram of a battery module containing a polyorganosiloxane foam material. DETAILED DESCRIPTION
[0007] The present invention is a battery module, which includes a housing containing an array of spatially separated battery cells and a barrier material contacting adjacent battery cells, wherein the barrier material comprises 35 wt% to 95 wt% of polyorganosiloxane foam based on the weight of the barrier material; 1 wt% to 30 wt% of a flame retardant; and 1 wt% to 35 wt% of hollow ceramic particles having a volume average particle size in the range of 25 μm to 300 μm; wherein the barrier material has a particle size of 0.10 g / cm 3 Up to 0.90g / cm 3 Density within the range.
[0008] Barrier materials as thermally insulating, flame retardant and compressible foamed polyorganosiloxanes can be prepared by modifying the method described in US Pat. No. 5,358,975. For example, polydimethylsiloxanes (a) functionalized with at least two, and preferably at least three Si-H groups are advantageously contacted with one or more hydroxyl-containing compounds (which are water, alcohols, diols, polyols) or compounds containing at least one silanol group (b), divinyl-functionalized polydimethylsiloxanes (c), hydrosilylation catalysts such as platinum-based catalysts (d), flame retardants (e) and hollow ceramic particles (f) to form a crosslinked network of insulating, compressible and flame retardant foamed materials having -Si-CH2-CH2-Si- groups and -Si-OR groups (where R is H or a structural unit (i.e., a reaction product) of an alcohol, diol, polyol or silanol). The total amount of components (a), (b) and (c) is from 35% or 40% to 80% or to 70% by weight of the polyorganosiloxane foam.
[0009] It may be advantageous to prepare the barrier material using a 2-part process, wherein in a first container, a first part of a divinyl-functionalized polydimethylsiloxane; a first part of a flame retardant; a hydrosilylation catalyst; one or more hydroxyl-containing compounds; and a first part of hollow ceramic particles are blended to form a Part A composition. In a second container, the remaining part of the divinyl-functionalized polydimethylsiloxane; a polymer resin blend, which is a mixture of a divinyl-functionalized polydimethylsiloxane and a crosslinked organopolysiloxane resin; the remaining part of the flame retardant; a polydimethylsiloxane functionalized with at least three Si-H groups; and the remaining part of the hollow ceramic particles are blended to form a Part B composition. Parts A and B are then combined and mixed, and then poured between two release film sheets to form the foamed material of the present invention.
[0010] The flame retardant is a metal hydroxide, carbonate, hydroxide-carbonate or hydrate that releases CO2 or water or both when heated. Examples of flame retardants include Al(OH)3, Mg(OH)2, Ca(OH)2MgCO3·3H2O (nesquehonite), Mg5(CO3)4(OH)2·4H2O (hydromagnesite), MgCa(CO3)2 (calcium carbonate), AlO(OH) (boehmite), NaHCO3 and hydrated MgSO4 (epsomite). The polyorganosiloxane foaming material contains 1 wt% or 2 wt% or 3 wt% to 30 wt% or to 20 wt% or to 15 wt% of the flame retardant based on the weight of the foaming material.
[0011] The barrier material also comprises 1 wt % or 5 wt % or 10 wt % to 35 wt % or to 30 wt % to 25 wt % of hollow, air-filled or inert gas-filled ceramic particles. As used herein, "ceramic" refers to a crystalline or semi-crystalline inorganic oxide, nitride, carbide, oxynitride or oxycarbide of a metal such as aluminum (e.g., crystalline or semi-crystalline Al2O3), silicon (e.g., crystalline or semi-crystalline SiO2) or calcium (e.g., crystalline or semi-crystalline CaO), or a combination thereof. Crystallinity can be measured by X-ray powder diffraction. As used herein, the term "semi-crystalline" refers to a ceramic material having amorphous regions and crystalline regions. The hollow ceramic particles have a volume average particle size of 25 μm or 50 μm or 70 μm to 300 μm or to 200 μm or to 150 μm, as measured using a dynamic light scattering analyzer such as a Beckman Coulter LS130 particle size analyzer. The resulting barrier material has a particle size of 0.10 g / cm 3 or 0.15g / cm 3 Up to 0.90g / cm 3 Or up to 0.50g / cm 3 Density within the range.
[0012] In another aspect, the present invention is a composition comprising, based on the weight of the composition, a) 2 to 50 wt% of a polysiloxane functionalized with at least two Si-H groups and having a degree of polymerization in the range of 5 to 1000; b) 1 to 50 wt% of water, an alcohol, a diol, a polyol, or a compound containing one or more silanol groups; c) 10 to 90 wt% of a polysiloxane functionalized with at least one ethylenically unsaturated group and having a degree of polymerization in the range of 20 to 2000; wherein the total concentration of components a, b and c ranges from 35 to 95 wt% based on the weight of the composition; d) a catalytic amount of a hydrosilylation catalyst; e) 1 to 30 wt% of a flame retardant; and f) 1 to 35 wt% of hollow ceramic particles having a volume average particle size in the range of 25 μm to 300 μm.
[0013] Figure 1 Represents one embodiment of the present invention. The battery module includes a housing (20) that houses an array of spatially separated battery cells (30 and 30a) and a barrier material (40) that contacts adjacent battery cells, thereby creating an insulating barrier between the battery cells (30). In this embodiment, the barrier material is positioned between adjacent battery cells (30). In another embodiment, the barrier material covers the battery cells. The battery module may also include an end plate (50) at the inner edge of the housing, which is in direct contact with the battery cells (not shown) or indirectly in contact with the battery cells through a barrier foam (30a). The barrier material can be inserted into the space between adjacent battery cells and between the cells and the end plate; alternatively, a foam precursor can be applied to the cell and into the space between the battery cells, and then cured to form the barrier material.
[0014] Examples of suitable battery cell designs include cylindrical, pouch, and prismatic cells. Particularly advantageous modules include pouch or prismatic cells with preformed barrier material in the form of foam sheets positioned between the cells during assembly. For cylindrical designs, a precursor foam material is typically dispensed into the spaces separating the cylindrical cells and then cured to form a barrier material surrounding the cylindrical cells.
[0015] It has been discovered that battery modules having barrier materials as described herein provide the desirable properties of thermal insulation, flame retardancy, and compressibility in rechargeable battery thermal barrier applications.
[0016] In the following examples, ViMe2SiO 1 / 2 / (CH3)3Si-O 1 / 2 / SiO 4 / 2 Resin M w and M nIt was determined by gel permeation chromatography (gpc) using a gpc column filled with divinylbenzene cross-linked polystyrene beads of pore type Mixed-C (Polymer Laboratory) of 5-mm diameter size. THF was used as the mobile phase and detection was performed by a refractive index detector.
[0017] Example 1 - Preparation of Foamed Organopolysiloxane Articles with Ceramic Particles
[0018] The first component (Part A) was prepared by mixing together using a Flacktek Speed mixer: dimethylvinylsiloxy terminated polydimethylsiloxane having a viscosity of about 40,000 mPas (Polymer 1, 11.3 pbw); 1) dimethylvinylsiloxy terminated polydimethylsiloxane having a viscosity of about 1,900 mPa·s and about 0.22 wt% Vi; and 2) ViMe2SiO 1 / 2 :(CH3)3Si-O 1 / 2 :SiO 4 / 2 The structural unit ratio is 5:40:55, M n is 5000 and M w 21,400 ViMe2SiO 1 / 2 / (CH3)3Si-O 1 / 2 / SiO 4 / 2 64:36 w / w blend of resin (polymer-resin blend, 64.9 pbw); and Micral 855 aluminum hydroxide (15.2 pbw). The contents were stirred at 2000 rpm for 30 seconds, after which a complex of Pt(0) and divinyltetramethyldisiloxane (0.93 pbw, 0.62 wt% Pt), 1,4-butanediol (2.6 pbw) and benzyl alcohol (3.3 pbw) were added to the mixture and the contents were stirred at 2000 rpm for 30 seconds. Finally, Elminas Spheres HCMS-W150 hollow ceramic particles (volume average particle size of 100 μm; 20 pbw) were added to the mixture and the contents were stirred at 2000 rpm for 30 seconds.
[0019] The second composition (Part B) was similarly prepared by mixing together Polymer 1 (8.9 pbw), polymer resin blend (51 pbw) and Hymod M855 aluminum hydroxide (26.4 pbw). The contents were stirred at 2000 rpm for 30 seconds, after which a linear organohydrogenpolysiloxane having a viscosity of 30 mPa·s and a 1.6 wt% SiH content (6.7 pbw) and a polydimethylorganohydrogensiloxane having a viscosity of 5 mPa·s and a 0.7 wt% SiH content (5.1 pbw) were added to the mixture and the contents were stirred at 2000 rpm for 30 seconds. Elminas Spherers HCMS-W150 hollow ceramic particles (20 pbw) were then added to the mixture and the contents were stirred at 2000 rpm for 30 seconds.
[0020] Equal amounts of Part A and Part B were then mixed and the mixture was poured between two release films (matte mylar film). The initial (pre-foaming) thickness was controlled at 0.045 inches using a nip roller. The sample was cured at 70°C for 5 minutes and then at 100°C for 15 minutes to produce a foam sheet for further testing. (Density = 0.31 g / cm 3 )
[0021] Example 2 - Preparation of Foamed Organopolysiloxane Articles with Ceramic Particles
[0022] In addition to using Elminas Spheres HCMS THERMO-W75 hollow ceramic particles (volume average particle size 80 μm, 20 pbw) (density = 0.31 g / cm 3 ), the method for preparing the foamed article of Example 1 is carried out in substantially the same manner.
[0023] Example 3 - Preparation of Foamed Organopolysiloxane Articles with Ceramic Particles
[0024] In addition to using Elminas Spheres HCMS-W300 hollow ceramic particles (volume average particle size 180 μm, 20 pbw) (density = 0.34 g / cm 3 ), the method for preparing the foamed article of Example 1 is carried out in substantially the same manner.
[0025] Thermal insulation and flammability
[0026] The thermal insulation and flammability of the foams prepared as described in the examples were tested using a hot plate set on a hydraulic press. The hot plate was set at 600°C with an insulator on top of the surface. Four thermocouples (type K) were fixed to an aluminum heat sink (4"×4"×0.47") using Kapton tape. The sample (4"×4") was then placed and fixed to the heat sink using Kapton tape. Another thermocouple (type K) was attached to the sample surface using Kapton tape. The insulator was removed from the hot surface, and the sample attached to the heat sink was quickly placed on the hot surface so that the sample surface faced the hot plate surface and the Al heat sink faced the opposite side. The pressure was quickly increased to 355kPa. The interface temperature between the hot plate surface and the sample surface and the interface temperature between the sample surface and the heat sink were recorded using a data logger. Once the time reached 300 seconds, the pressure was released and the test was terminated. Sample surface temperatures of <300°C were considered acceptable. No observable flames throughout the test were considered acceptable flame retardancy.
[0027] hardness
[0028] Measure hardness using a Shore 00 durometer. Place the test specimen on a hard, flat surface. Then press the indenter of the Shore 00 durometer onto the specimen, making sure it is parallel to the surface. Read the hardness during firm contact with the specimen. A hardness of <80 is considered acceptable.
[0029] Compression force
[0030] The compressive force was measured using a TA.HDplus Texture Analyzer equipped with a 100kg load cell, a 40mm diameter aluminum probe, and a flat heavy-duty aluminum substrate. The silicone foam sample was cut into a circle using a 1" diameter die cut and placed between the substrate and the probe. The probe was initially set at the same height as the sample thickness and lowered at a rate of 1mm / s until the pressure reached a maximum. The sample thickness and pressure were recorded as a compression force curve. The pressure was recorded at 30% of the initial sample thickness. A compression force of <500kPa was considered acceptable.
[0031] Foam density
[0032] The foam density was calculated based on the average thickness and weight of two foam samples having a diameter of 1 inch.
[0033] The properties of the ceramic-filled organopolysiloxane article were compared to a commercial organopolysiloxane article (COHRlastic silicone foam, available from Stockwell Elastomerics) that was similar in construction to the example foams except that it did not contain hollow ceramic particles.
[0034] Table 1 is a summary of the performance properties of the foams of Examples 1 to 3 and commercial comparative foams. Density is in g / cm 3 Measurements; hardness is measured in Shore 00 units; compression (Force) is measured in kPa at 30% compression; temperature at 600°C (T after 300 seconds) refers to the sample surface temperature after 300 seconds; and flammability refers to the observability of flames during the thermal insulation test.
[0035] Table 1 - Properties of organopolysiloxane products
[0036] characteristic standard Compare Example 1 Example 2 Example 3 density <0.9 0.23 0.31 0.31 0.34 hardness <80 35 65 69 71 force <500 17 246 306 300 Temperature after 300 seconds <300℃ 334℃ 246℃ 255℃ 294℃ Flammability No flame No flame No flame No flame No flame
[0037] Table 1 shows that the barrier material used in the battery module of the present invention passed all tests, while the commercial example failed the thermal insulation test. It has been surprisingly found that the barrier material with hollow ceramic particles reduces the surface temperature at 300 seconds without adversely affecting other key properties of the foam. It has also been found that hollow ceramic particle sizes in the range of 50 μm to 150 μm are particularly effective in reducing the surface temperature.
Claims
1. A battery module comprising a housing containing an array of spatially separated battery cells and a barrier material contacting adjacent battery cells, wherein the barrier material comprises, based on the weight of the barrier material, 35% to 95% by weight of a polyorganosiloxane foam; 1% to 30% by weight of a flame retardant; and 1% to 35% by weight of hollow ceramic particles having a volume average particle size in the range of 25 μm to 300 μm; wherein the barrier material has a particle size of 0.10 g / cm 3 to 0.90g / cm 3 Density within the range. 2 . The battery module according to claim 1 , wherein the barrier material comprises 50 wt % to 80 wt % of the polyorganosiloxane foam and 2 wt % to 20 wt % of the flame retardant.
3. The battery module according to claim 2, wherein the flame retardant is Al(OH)3, Mg(OH)2, MgCO3·3H2O, or Mg5(CO3)4(OH)2·4H2O, MgCa(CO3)2, AlO(OH), NaHCO3 or hydrated MgSO4 or a combination thereof.
4. The battery module according to any one of claims 1 to 3, wherein the barrier material has a thickness of 0.15 g / cm 3 to 0.50g / cm 3 Density within the range. 5 . The battery module according to claim 4 , wherein the hollow ceramic particles have a volume average particle size in the range of 25 μm to 200 μm as measured by dynamic light scattering. The battery module according to claim 4 , wherein the hollow ceramic particles have a volume average particle size ranging from 50 μm to 150 μm as measured by dynamic light scattering.
7. The battery module according to any one of claims 5 or 6, wherein the hollow ceramic particles are crystalline or semi-crystalline Al2O3 particles, crystalline or semi-crystalline SiO2 particles, or crystalline or semi-crystalline CaO particles, or crystalline or semi-crystalline Al / Mg / Ca silicates. 8 . The battery module of claim 1 , comprising pouch-shaped or prismatic battery cells and a sheet of the barrier material positioned between adjacent battery cells. 9 . The battery module of claim 1 , comprising cylindrical battery cells, wherein the barrier material surrounds the cylindrical battery cells.
